ANALISIS RASIO KETERGANTUNGAN TERHADAP PEREKONOMIAN PROVINSI BANTEN - Chika Aisyah Putri Setianto; Sumiyarti Sumiyarti (STMIK Widuri Jakarta, 2024)
Gross Regional Domestic Product (GRDP) is the main indicator to assess the economic condition of a region. The increase in GRDP reflects economic growth, and vice versa. This study aims to examine the effect of Dependency Ratio, Human Development Index (HDI), Gross Fixed Capital Formation (PMTB), Regional Expenditure, and Gini Ratio on GRDP in Banten Province. The data used comes from the Central Statistics Agency and other sources, with a time series period of 2015-2023 and a cross-section covering 8 districts/cities in Banten Province. The results of the study indicate that partially, the Dependency Ratio and Gini Ratio have a negative effect on GRDP, while HDI, PMTB, and Regional Expenditure have a positive effect. Simultaneously, at least one variable has a significant influence on Banten's GDP. All independent variables are able to explain 99.99% of the variation in GRDP, while the remaining 0.01% is influenced by other factors not included in the model.